Warranty subskrypcyjne jako instrument pozyskiwania kapitału przedsiębiorstwa - Błach, Joanna (Subscription Warrants as a Source of Corporate Finance, 2006)
The company can obtain additional finance by issuing stock-purchase warrants. The holder of the warrant has the right, but no the obligation, to buy new ordinary shares in a company at a future date, at a fixed, predetermined price. The warrants can be attached to the company's shares or bonds to make the issue more attractive to investors. They can be also separated from the underlying stock and traded on the market in their own right. Stock purchase warrants can be used as one of the alternatives to cash dividents pay out to the shareholders which enables company to retain higher profits. They can be also used as an additional premium for the managers and employees in order to lower the agency costs. The process of issuing and exercising stock-purchase warrants may influence a lot of different aspects of company's activity. Therefore, the decision of using warrants requires thorough analysis of advantages and disadvantages connected with them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 83-93